2020
DOI: 10.3390/atmos11101098
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution-Related Brain Metal Dyshomeostasis as a Potential Risk Factor for Neurodevelopmental Disorders and Neurodegenerative Diseases

Abstract: Increasing evidence links air pollution (AP) exposure to effects on the central nervous system structure and function. Particulate matter AP, especially the ultrafine (nanoparticle) components, can carry numerous metal and trace element contaminants that can reach the brain in utero and after birth. Excess brain exposure to either essential or non-essential elements can result in brain dyshomeostasis, which has been implicated in both neurodevelopmental disorders (NDDs; autism spectrum disorder, schizophrenia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 479 publications
0
8
0
Order By: Relevance
“…Such an understanding can guide the development of more realistic focused animal exposure models of human AP exposure as well as allow refinement of epidemiological studies, and, consequently, a more meaningful approach to mechanistic studies. In addition, it would be potentially informative in population studies, for example, using geographic mapping of exposures to various metal contaminants of AP, along with gases such as SO 2 , where available, in relation to diagnostic or incidence data for various neurodevelopmental disorders and neurodegenerative diseases [ 30 ]. Such studies would also point to potential intervention strategies for neurodevelopmental disorders and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an understanding can guide the development of more realistic focused animal exposure models of human AP exposure as well as allow refinement of epidemiological studies, and, consequently, a more meaningful approach to mechanistic studies. In addition, it would be potentially informative in population studies, for example, using geographic mapping of exposures to various metal contaminants of AP, along with gases such as SO 2 , where available, in relation to diagnostic or incidence data for various neurodevelopmental disorders and neurodegenerative diseases [ 30 ]. Such studies would also point to potential intervention strategies for neurodevelopmental disorders and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of filters from exposure chambers in our studies revealed the presence of multiple metals and trace elements in the AP exposures that could lead to brain metal dyshomeostasis [ 30 ]. Iron (Fe) is the metal of greatest abundance in the atmosphere [ 31 ] and thus is often a dominant component of the trace element levels of particulate matter, with concentrations clearly differing by geographical and industrial source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After intratracheal instillation of mice with coal and coal fly-ash, Cr, Fe and Ni were detected in liver, spleen and brain [156] PM and associated metals have been linked to neurotoxicity and mental health [157]. Excess brain exposure to either essential or non-essential elements can result in brain dyshomeostasis, which has been implicated in both neurodevelopmental disorders (NDDs; autism spectrum disorder, schizophrenia, and attention deficit hyperactivity disorder) and neurodegenerative diseases [158]. After prenatal exposure of mice to concentrated ambient particles via inhalation, Fe, Al, and Si were metabolically distributed to the CNS [159].…”
Section: Translocation Of Inhaled Metals From Lungs To Other Organsmentioning
confidence: 99%
“…Although numerous investigations have been devoted to the elucidation of the ND pathologies, their primary causes continue elusive. Some interrelated crucial aspects on the progression of these disorders are proteopathy [6][7][8] , metal ion dyshomeostasis , environmental pollutants, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and neurotransmitter deficiencies. A chemical phenomenom shared by all these diseases is oxidative stress (OS).…”
Section: Introductionmentioning
confidence: 99%